The Museum of (Non)Remembrance. A Horse and the Warsaw Uprising Museum - Lorenc, Magdalena (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2017)
The permanent exhibition at the Warsaw Uprising Museum, which has been on display since 2004 (continuously since 2005) is a text of culture – a construct that is not free from power and politics. The political nature of the Museum does not, however, determine its value, but rather represents a diagnosis of the social reality where culture is a space of ideological confrontation. The view that the Museum is politically entangled in organisational and ideological terms is neither demeaning nor ennobling for a cultural institution. However, it requires that the Museum surrender its claims of neutrality in a situation where, by decision of its creators, it occupies a defined position in the discourse, as illustrated by the omission of the history of animals – victims of war – in the exhibition. Meanwhile, the new humanities provide the new museum (and also the traditional one) with trends that unmask the author of the narrative and demystify the objective nature of that narrative. They allow us not only to identify and explain the reasons why the WUM left out the wartime history of animals, but also to show how and why those issues should be thought about, discussed and presented in a different way.

Prezentowana od 2004 roku (nieprzerwanie od 2005 roku) wystawa stała w Muzeum Powstania Warszawskiego jest tekstem kultury – konstruktem niewolnym od władzy i polityki. Polityczność Muzeum nie przesądza jednak o jego wartości, a jedynie stanowi diagnozę rzeczywistości społecznej, w której kultura jest obszarem konfrontacji ideologicznej. Teza, że Muzeum jest uwikłane politycznie pod względem organizacyjnym i ideologicznym, nie jest deprecjonujące ani nobilitujące dla instytucji kultury. Wymaga jednak od Muzeum rezygnacji z roszczeń do neutralności, w sytuacji w której, decyzją swoich twórców, zajmuje ono w dyskursie określoną pozycję, czego przykładem jest pominięcie na ekspozycji historii zwierząt – ofiar wojny. Tymczasem nowa humanistyka oferuje nowemu muzeum (ale i tradycyjnemu) nurty, które demaskują twórcę narracji i demistyfikują jej obiektywny charakter. Pozwalają one zobaczyć i wyjaśnić powody pominięcia wojennej historii zwierząt w MPW, ale i wskazać, jak można i dlaczego powinno się inaczej o tych kwestiach myśleć, mówić i je pokazywać.
Muzeum (nie)pamięci. Koń a Muzeum Powstania Warszawskiego
Keywords: a “narrative” museum; „muzeum narracyjne”; the Warsaw Uprising Museum; Muzeum Powstania Warszawskiego; the wartime history of animals; wojenna historia zwierząt